Efeitos do treinamento em neurofeedback na atenção e nos estados afetivos de estudantes universitários não diagnosticados com transtornos clínicos - Silva, Jade Carvalho da (2021)
Neurofeedback presents itself as a technique of non-invasive neurophysiological selfregulation, in which the computer provides live feedback on the individual's brain activity from brain wave signals captured by electroencephalography. This technique proves to be socially advantageous, as it is an alternative to psychopharmacological interventions and provides real-time information about brain activity to facilitate brain wave modulation and improvement of cognitive processes. While attention refers to the ability to select certain stimuli among various distractors over a period of time, positive and negative affects refer to the individual's self-assessment about their affective state. There is an incipient literature in testing the effectiveness of new brain-machine interface systems, such as games, for improving attention and affective states in college students not diagnosed with clinical disorders. Considering this information, this study can contribute to the empirical and social validation of the neurofeedback intervention to improve attention and affective states in this population. The objective of this dissertation is to describe the effectiveness of neurofeedback as an intervention technique in the context of cognitive performance in non-clinical populations and to verify the feasibility of game-based neurofeedback training for the reduction of theta-beta ratio in two sessions in college students not diagnosed with clinical disorders. The study 1, presented in article format, performed a systematic review of neurofeedback studies to increase cognitive performance in healthy individuals available in the Web of Science, BVSalud, PsycInfo, Redalyc and Scielo databases, published between 2014-2020. In study 2, also presented in article format, the quantitative methodology with quasi-experimental design was adopted and the participants were assigned to the conditions of training with neurofeedback (experimental group) and training with pseudofeedback (active control group). Twelve undiagnosed college students with clinical disorders were recruited. In the screening stage, the registration form was used to obtain sociodemographic information and clinical history of the participants. The Psychological Battery for Assessment of Attention (BPA) and the Positive and Negative Affect Scale (PANAS) were used to assess attention and affective states. The protocol for decreasing the theta-beta ratio in the F3 region was used. The groups underwent two training sessions lasting 30 minutes each over a week. Statistical analyzes were performed using IBM SPSS Statistics 24 software. Results from study 1 suggest high effect on working memory, mood and sleep quality; medium to large effect for executive functions, and low to high effect for attention. The results of study 2 did not show significant differences in the mean value of theta-beta ratio between groups and sessions (p > 0.05). The participant with the highest level of attention indicated a decrease in theta-beta ratio in the experimental group (p <0.001). The participant who had a very high level of positive affect showed a decrease in theta-beta ratio in the second session compared to the participant who had a low level of positive affect in the NFT group (p < 0.04). There was a higher level of neuromodulation in the experimental group, but the active control group also managed to neuromodulate theta-beta in F3. Neurofeedback presents itself as a growing field with mixed results regarding its validity to improve attention and emotional regulation, and the effect of the intervention carried out in this study was low between groups and sessions. Despite the limiting factors discussed, this study glimpsed the potential of EEGneurofeedback as an efficient mechanism for increasing attention and emotional regulation.